Recent advances in bacteria-mediated cancer therapy - Liang, Shuya; Wang, Chao; Shao, Yingchun; Wang, Yanhong; Xing, Dongming; Geng, Zhongmin (Frontiers in Bioengineering and Biotechnology, 2022)
Cancer has been regarded as the leading cause of deaths worldwide. Although conventional therapies have been applied for fighting against the cancer, the poor oxygen, low extracellular pH and high interstitial fluid pressure of the tumor microenvironment make these treatments fail to completely eradicate cancer cells. Recently, bacteria have been increasingly being considered as a promising platform for cancer therapy due to their many unique properties, such as specific tumor targeting, high motility, immunogenicity and gene or drug carriers. Thus, various types of bacteria have been already used for solid and metastatic tumors therapies with promising results. In addition, with the development of synthetic biology, engineered bacteria have been endowed controllable expression of therapeutic proteins. Meanwhile, nanomaterials have been widely used to modify bacteria for target drug delivery, PTT, magnetothermal therapy and PDT, while promoting antitumor efficiency of synergistic cancer therapies. In this review, a brief introduction of the foundation of bacterial biotherapy is provided. We summarize recent advances of many different types of bacteria used in multiple targeted tumor therapies, and then discuss the future prospects of bacteria-mediated cancer therapies.